Environmental Impacts of Plant-Based Diets: How Does Organic Food Consumption Contribute to Environmental Sustainability? - Lacour, Camille; Seconda, Louise; Allès, Benjamin; Hercberg, Serge; Langevin, Brigitte; Pointereau, Philippe; Lairon, Denis; Baudry, Julia; Kesse-Guyot, Emmanuelle (Frontiers in Nutrition, 2018)
Background: Studies investigating diet-related environmental impacts have rarely considered the production method of the foods consumed. The objective of the present study, based on the NutriNet-Santé cohort, was to investigate the relationship between a provegetarian score and diet-related environmental impacts. We also evaluated potential effect modifications on the association between a provegetarian score and the environmental impacts of organic food consumption. Methods: Food intake and organic food consumption ratios were obtained from 34,442 French adults using a food frequency questionnaire, which included information on organic food consumption for each group. To characterise the overall structure of the diets, a provegetarian score was used to identify preferences for plant-based products as opposed to animal-based products. Moreover, three environmental indicators were used to assess diet-related environmental impacts: greenhouse gas (GHG) emissions, cumulative energy demand (CED) and land occupation. Environmental impacts were assessed using production life cycle assessment (LCA) at the farm level. Associations between provegetarian score quintiles, the level of organic food consumption and environmental indicators were analysed using ANCOVAs adjusted for energy, sex and age. Results: Participants with diets rich in plant-based foods (fifth quintile) were more likely to be older urban dwellers, to hold a higher degree in education and to be characterised by an overall healthier lifestyle and diet. A higher provegetarian score was associated with lower environmental impacts (GHG emissionsQ5vsQ1=838/1,664 kg CO2eq/year, -49.6%, P<0.0001; CEDQ5vsQ1=4,853/6,775 MJ/year, -26.9%, P<0.0001; land occupationQ5vsQ1=2,420/4,138 m2/year, -41.5%, P<0.0001). Organic food consumption was also an important modulator of the relationship between provegetarian dietary patterns and environmental impacts but only among participants with diets rich in plant-based products. Conclusion: Future field studies should endeavour to integrate all the components of a sustainable diet, i.e., both diet composition and production methods.